Red dragon fruit (Hylocereus polyrhizhus) in preventing collagen decrease in menopause induced rats skin - Eswariy Chandramogan; I Wayan Sugiritama; I Gusti Ayu Dewi Ratnayanti; I Gusti Nyoman Sri Wiryawan; Ida Ayu Ika Wahyuniari (Neurologico Spinale Medico Chirurgico, 2020)
Background: Skin aging in menopause women was due to fewer collagen numbers in cells and antioxidants are necessary for inhibiting the process of skin aging due to oxidative stress. Red dragon fruits which plant in Indonesia was known to have a high concentration of antioxidants. This study aimed to assess the ethanol extract of red dragon fruit skin effects on the number of collagens on the skin of female Wistar rats which has been ovariectomized. Methods: This experimental research was a post-test only control group design that was conducted on 30 female Wistar rats. Groups were divided into control (P0), 5% ethanol extract (P1), and 15% ethanol extract concentrations (P2). The dosage was given orally to the 30 female rats and left for observation for 30 days. The number of collagens was observed and calculated on visual evaluation of the skin biopsy under a light microscope. Results: The result showed a significant difference between treatment groups and control (p<0.05). The number of collagen are higher in P2 (83.03 ±4.84) and P1 (77.26 ±5.06) than P0 (57.73 ±5.04). Conclusion: Ethanol extract of red dragon fruit skin could increase the number of collagen in rat skin.